(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The massively increased cases of Covid-19 have caused a major issue to the world and have raised noteworthy health concerns to the society across the glove. Two hundred ten countries and territories including many developing countries are facing limitless burden due to this infectious diseases. Every day we are witnessingincreasing number of reporting cases.So development of an expectation model can help to identify the outbreak sequence. This paper givers a concise idea and outlines a mathematical model using von Bertalanffy growth function (VBGF) to Forecasting of Covid-19 outbreak and analysing of details of parameters which will help other researchers to understand and determine the epidemic trend of the outbreak which can further be used for, country readiness, infection prevention, control and risk communication, and also readiness for clinical management.In this mathematical modelling, we translate those factors into the language of mathematics to make scientiﬁc understanding more clearly.